Patterns of drug use and drug dispensing in dermatology outpatient prescriptions in a tertiary care teaching hospital - Kumar, Aravinda (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Periodic assessment of drug prescribing and dispensing pattern in a hospital facility shall play a major role in avoiding the inappropriate use of drugs which leads to potential hazards and expenses for the patients. Methods: The objective of the study was to analyse the patterns of drug use and dispensing in dermatology outpatient prescriptions from a tertiary care teaching hospital in south India. Data were collected over a period of one month from patients attending dermatology outpatient department by scrutinizing 100 prescriptions and analyzed using WHO formulated “core drug use indicators” like the format, prescribing pattern and rationality of prescriptions. Results: The total number of drugs prescribed in 100 prescriptions was 233 i.e. on average 2.33 drugs were prescribed per patient. The patient’s name and age were mentioned in all the prescriptions while diagnosis, dose, route of administration, dosage form, duration of therapy and prescriber’s identity was written in 43.29%, 68.04%, 69.07%, 100%, 49.48% and 63.91% prescriptions respectively. Out of all drugs, 42.91% were generic drugs and 57.08% were from National Essential Drug List of India. Steroids (18.02%) were the most common group of drugs used, followed by keratolytics and emollients (15.87%). Most of the drugs were given by topical route (47.63%). Conclusions: A prescription by a doctor is a reflection of physicians’ attitude towards the disease and the role of drug in its treatment. It also provides an insight into the nature of health care at that facility. Interventions to rectify over proper prescription format and prescription of generic drugs are necessary to further improve rational drug use in this facility.